IDDF2018-ABS-0078 Long-term survival and prognostic factors of hepatocellular carcinoma after radiofrequency ablation with cool-tip electrode: prospective result in 105 patients. (June 2018) - Thu Huyen, Nguyen Thi; Bang, Mai Hong; Riep, Tran Van; Thinh, Nguyen Tien
Abstract : Background: Radio-frequency ablation (RFA) has been indicated as a curative treatment for early-stage hepatocellular carcinoma (HCC). This study was to assess the long-term survival result and analyse risk factors of percutaneous Radiofrequency Ablation with Cool-tip in HCC patients. Methods: A prospective study involved 105 cirrhotic HCC patients (mean tumour size:32, 5±11, 3 mm) underwent percutaneous RFA using Cool-tip RF electrode (COOL-TIP E SERRIES, COVIDIEN) at the 108 hospital, from September 2012 to December 2017). The Kaplan-Meier curves and the multivariate Cox regression analysis were used to assess the prognostic factors. Results: The progression-free survival (PFS) was 23.6±1.2 months and the overall survival (OS) was 40.3±0.74 months. The cumulative 1 year, 2 year, 3 year, 4 year survival probability were 98%; 95.2%; 87, 3% and 70, 1 respectively. The PFS was related to tumour morphology, HCC differentiation BCLC staging. The OS were affected by tumour characteristics, number of tumour, AFP response, and tumour complete response. Pre-treatment elevated AFP, multifocal HCCs, non-response AFP, in-complete tumour necrosis were negative prognostic factors for long-term survival. The OS and survival rates were also related to Child Pugh class and stage of tumour. At multivariate analysis (Cox Survival Analysis) tumour size and liver function (Chil-Pugh class) were independent significant predictors of overall patient survival. Conclusions: RFA with Cool-tip electrode is effective for HCC patients; the long-term survival result depends on some prognostic factors before treatment.